STRATEGIES TO DEVELOP MODERN COURSE FOR FUTURE TEACHERS: PERSON-CENTRED APPROACH - Kushnir Н.О.; Manzhula А.М.; Valko Н.В. (Journal of Information Technologies in Education (ITE), 2013)
The chapter’s authors describe the specialties and potential of today generation students,challenges in retaining them in teaching profession. The teaching and developing course strategies are also proposed to handle with tech savvy students in ICT and other courses;